Analisis Keakuratan Kualitas dan Kuantitas Sustainability Report Disclosure; Strategi Menarik Minat Investasi di Bank Syariah Indonesia - Maulana, Nora (Jurnal Magister Ekonomi Syariah, 2022)
Advances in digital technology that penetrase so quickly create serious changes in various fields including the economy. Sustainability report disclosure is one of the crucial issues that is interesting and always hotly discussed by economic actors in the 5.0 era, including sharia economic actors. This research is important because the accuracy of the sustainability report disclosure is not only a form of compliance with sharia values but also as a trend of needs for stakeholders, and becomes an added value for companies including Bank Syariah Indonesia (BSI) in order to reach wider stakeholders and investors. Increasing the accuracy of the quality and quantity of the sustainability report disclosure can be a solution for BSI in developing its Islamic finance industry. As for the research objectives; First, knowing the effect of the accuracy of the quality and quantity of the sustainability report disclosure on financial performance; Second, knowing the impact of the quality and quantity of the sustainability report disclosure on investor interest in investing. This research is a type of field research with a mix method. The sample was determined through purposive sampling and obtained as many as 34 respondents. The research data used are primary data and secondary data, while the data collection method is done through questionnaires, interviews and documentation. The analysis technique was carried out by using multiple linear regression, t test, F test, and R-Square test. The results of the study show that the accuracy of the quality and quantity of the sustainability report’s disclosure, either partially or simultaneously, has a positive and significant effect on investment interest, as evidenced by the probability statistics obtained, namely 0.000 < 0.05. Both variables have an effect of 94,3% on interest in investing. From the results of the study, it is also known that the variable quality of sustainability report disclosure is the dominant variable that influences the level of investor interest in investing with the value obtained reaching 1.254085 on investors in the Valu Capital stock community in Banda Aceh.